Company Size, Profitability, Tangibilitas, Free Cash Flow, And Growth Opportunity That Affect The Capital Structure In Manufacturing Company - Ambrosius Fabian Chandra (Jurnal Manajemen Bisnis dan Kewirausahaan, 2019)
The purpose of this research is to find the influence of company size, profitability, structure of assets, free cash flow, and growth opportunity towards capital structure in manufacturing company that listed in Indonesian Stock Exchange. The population of this research is manufacturing company that listed in Indonesian Stock Exchange in the period 2013-2015. The sampling technique used is purposive sampling method. Multiple regression analysis techniques was used in analyzing the data. The level of significance used to examine the regression is 5%. The results of this research conclude that tangibilitas, free cash flow, and growth opportunity have effect on capital structure. company size, and profitability have no effect on capital structure ratio. The result from f test indicates that the data used and the reggresion model fit in this research.